An analytical model of tumour response to radiotherapy to investigate biological parameters of chordoma treated by X-rays, protons and carbon ions. (September 2016) - Kanellopoulos, Vassiliki; Kirkby, Norman F.; Jena, Rajesh; Dosanjh, Manjit; Kirkby, Karen J.
Abstract : Introduction: At present, cancer treatment protocols are mostly evidence-based while deducted from clinical trials and applied to other patient groups. Cancer modelling could be an alternative tool, hence there is a strong need to develop models which capture essential interactions and help to understand treatment outcome better. Purpose: Clinical data is commonly used to extract information on patient level of survival or regression probabilities for a certain treatment set-up. This study introduces a mathematical model which allows to acquire a deeper insight on biological properties of a tumour using clinical data of patients treated with conventional radiotherapy and particle therapy. Materials and methods: We introduce a physiological tumour growth model combined with a treatment model considering different cell radiosensitivities for proliferating and quiescent cells. A patient population model is constructed expecting biological parameters can be sampled from probability distributions. Using Monte–Carlo simulation the model parameters can be fitted to data from clinical trials. Results: The model is applied to recurrence curves of chordoma following radiotherapy with X-rays, protons and carbon ions. The probability distribution of radiosensitivities of tumour cells treated by different beam qualities is determined, showing a narrowing of the distribution width and a higher mean sensitivity towards high LET radiation. Conclusion: Results could be used to assist in designing clinical trials and predict clinical outcome for individual patients, in particular give treatment indications for hadron therapy. Disclosure: None.